PENGARUH PENAMBAHAN BUNGA KECOMBRANG TERHADAP DAYA TERIMA DAN KANDUNGAN GIZI KERUPUK - Molerman '; Noviar Harun; Evy Rossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The objective of this study was to obtainthebestpercentage of torch gingerflowerforuse inmaking ofcrackers. This research wascarried outexperimentally usingcompletely randomized design(CRD) withfivetreatments, namely: K1(torch gingerflower0%); K2(torch gingerflower10%); K3(torch gingerflower15%); K4(torch gingerflower20%) andK5(torch gingerflower25%). The results showedthat thetreatmentlevel oftorch gingerflowerusein the making ofcrackerssignificant effecton ash, protein, calciumlevels of itandinflating power of crackersas well asorganolepticassessment, namely thecolor, aroma, flavorandcrispness, butnot significanteffecton thewater contentandthe overallassessment of crackers. Thetreatment ofK5(torch gingerflower25%) resulted ina bettercrackerswithash content5.06%, protein1.38% 29.31mg/100gcalcium, inflating power of crackers 54.67%, slightlybrowncolor, lessdistinctivetorch gingerflower aroma, typical flavor of torch gingerflower andlesscrisp, and the overallassessmentof thiscrackerwaspreferredby thepanelists.   Keyword: crackers, torch ginger flower